Adding efficiency to proficiency: a study of trainee polypectomy efficiency metrics - Muething, Larissa; Wani, Sachin; Hall, Matt; Simon, Violette; Ezekwe, Ezenwanyi; Nguyen-Vu, Tiffany; Malvar, Carmel; Duloy, Anna; Kaltenbach, Tonya; Keswani, Rajesh; Patel, Swati G. (Endoscopy, 2020)
Background Although validated colonoscopy assessment tools exist, they do not measure efficiency. This study aimed to assess content validity of polypectomy efficiency (PE) and neoplastic polypectomy efficiency (NPE) as colonoscopy efficiency indices.Methods Data from a randomized controlled trial evaluating polypectomy among gastroenterology trainees were utilized. PE and NPE were defined as number of polyps (or neoplastic polyps) removed/withdrawal time × 100. Content validity was assessed by determining the association between efficiency indices and polypectomy times. Results 20 trainees performed 601 colonoscopies. There was a strong association between PE/NPE and actual polypectomy times: as polypectomy time increased by 1 minute, the PE decreased by 0.48 (P = 0.001) and NPE decreased by 0.24 (P = 0.03). Conclusions The study proposed and provided content validity for PE and NPE as colonoscopy efficiency indices.